Efeitos da realidade virtual para treino de habilidades motoras e cognitivas em idosos institucionalizados - Soares, Mariana Cristina (Universidade Federal de São Carlos, 2014)
With advancing age, there is a tendency of loss of cognitive aspects such as memory, attention, learning new technologies and motor aspects such as loss of range of motion of the upper limbs. The literature points to investments made to investigate the use of virtual reality in cognitive and motor aspects, however, due to the few researches found on the topic, is one notable gap in terms of describing the training of motor skills of the member and higher cognitive skills using virtual reality applications. This research aimed to evaluate the use of virtual reality application KapMan® for training of motor skills of upper member and cognitive in institutionalized elderly. The research was performed in a long - term institution, located in a midsize city in the state of São Paulo. The participants in this study were six seniors and we used a questionnaire about participants - to make sure about their skills and understanding about the game - measurement of range of motion, heart rate and blood pressure, the DASH questionnaire was used and Mini - mental State Examination. Furthermore, adaptations in the original game KapMan® were made. The results indicated a reduction in execution time of activity between the first and last time, and an increase of the final score (score) obtained, leading to believe that the adjustments made in the game and the training of the proposed activity resulted in better performance of the elderly. There were no observable changes in variables heart rate and blood pressure. The data shows an improvement in pain and upper limb function, and increased range of motion of the upper limb of the elderly. As the cognitive aspects, four elderly have compatibility with cognitive disabilities and two do not have this loss. Nevertheless, the elderly understood, learned and developed motor skills of the upper limb and cognitive training with the proposed activity. Thus, the premise that the deployment of virtual reality applications help the training of motor skills and cognitive upper limb was confirmed.
Keywords: Reabilitação; Capacidade motora; Cognição; Realidade virtual; Idosos; Virtual reality; Senior; Motor and cognitive rehabilitation; OUTROS